Self-Report Methods for Assessing Emotions: Understanding Structure and Accuracy of Measurement - Onur Çalışkan; Aycan Kapucu (Psikoloji Çalışmaları)
Emotion is structurally multifaceted with different components. One of these components, subjective experience, is pivotal in defining and measuring emotions. Self-report methods are used to ascertain the subjective experience of emotion. Unlike the neural and behavioral components of emotion, the qualities in subjective experience have been analyzed relatively less. However, for a more accurate and valid determination, the relevant structure should be well conceptualized. In this sense, the first part of this review precisely refers to the concept of emotional experience. This section concerns the distinctive meaning of subjective experience and details the correlation of subjective experience with other components of emotion. Next, the methods of accessing and expressing this experience will be discussed. Finally, the various scales in literature for measuring subjective experience are discussed. The status of these scales in Turkish and international literature is summarized. After conceptualizing subjective experience, the second part includes crucial aspects that may be useful for a more accurate and valid measurement. For this purpose, temporal issues that are important in measurement are addressed. First, the results of the temporal position of measurement, which may be in the past, future, or online; the results of the differences in the temporal emphasis in the instruction and the mechanism by which it affects the determination are mentioned. Subsequently, systematic explanations of individual differences in the experience of emotion are emphasized. Emotional granularity, referring to the extent to which an emotion is expressed in detail, and emotional dialecticism, indicating the state of experiencing different emotions together, are explained. Individual differences and their potential contribution to measuring and understanding emotion were addressed. The different views on the subjective experience of emotion, the temporal aspects, individual differences that can matter for measurement, and the mechanisms by which they can contribute to determination practices were discussed.